2008
DOI: 10.1002/maco.200804120
|View full text |Cite
|
Sign up to set email alerts
|

Development of thermal sprayed layers for high temperature areas in waste incineration plants

Abstract: Corrosion and wear in the hot gas area of thermal energy plants are severe problems, which often cause premature damage of components. In general, the most components of plants are made of materials, which are not stable under corrosive conditions. For corrosion protection (and also wear protection) and lifetime extension of these components, coatings with more resistant materials are applied. Because of the high concentration of corrosive species and the alternating composition of the atmosphere near to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…An alternative approach is to use APS-applied multilayer coatings as durable corrosion inhibitor materials. Corrosion tests within a WTE plant with internally cooled test probes (450 • C) of a steel tube (St 37.8/1.0345) as substrate material, coated with Inconel 625 as the bond-coat and yttria-stabilized zirconia (YSZ) as the top-coat, showed an improved corrosion resistance [13]. This material combination was placed in a WTE plant in a flue gas temperature range between 680 and 740 • C for 500 h (~21 days).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach is to use APS-applied multilayer coatings as durable corrosion inhibitor materials. Corrosion tests within a WTE plant with internally cooled test probes (450 • C) of a steel tube (St 37.8/1.0345) as substrate material, coated with Inconel 625 as the bond-coat and yttria-stabilized zirconia (YSZ) as the top-coat, showed an improved corrosion resistance [13]. This material combination was placed in a WTE plant in a flue gas temperature range between 680 and 740 • C for 500 h (~21 days).…”
Section: Introductionmentioning
confidence: 99%
“…In light of this challenging scenario, several authors have pursued efficient coatings to prevent the high temperature corrosion of metallic materials in biomass fueled boilers and waste incinerators [114][115][116]. Hearley et al [117] showed that coatings produced by the high velocity oxygen fuel (HVOF) thermal spray process form effective barrier against high temperature corrosion.…”
Section: Coatingsmentioning
confidence: 99%
“…A large number of coating processes are available to provide surface protection [24]. Several authors have pursued efficient coatings to prevent the high-temperature corrosion of metallic materials in biomass fuelled boilers and waste incinerators [25][26][27].…”
Section: Introductionmentioning
confidence: 99%